Development of Blended Learning Radio and Television System Engineering on Audio-Video Engineering Expertise Competence (Universitas Negeri Semarang, 2022)
The explanation of the National Education System Law Number 20 concerning the National Education System (2003) states that vocational education is secondary education that prepares students to work in specific fields. This study aims to compile test the feasibility, validity, and effectiveness of the Blended Learning model in Radio and Television System Implementation (PSRT) in the competence of Audio-Video Engineering expertise at Public Vocational High School 3 Semarang. Research and development use the analysis, design, development, implementation, evaluation (ADDIE) model. This research aims to describe in detail the stages of planning, implementation, and effectiveness of the blended learning model. It shows that learning using the flipped classroom blended learning model can improve student outcomes. In general, learning activities have been carried out correctly and optimally. This can be seen from the results of the average implementation of meeting 1 = 83 (good category), meeting 2 = 85 (good category), meeting 3 = 88 (very good category), and meeting 4 = 90 (very good category). The average is 86.5, with a good category if taken based on the results above. An average of 86.5 shows that the implementation of learning with the blended learning flipped classroom model in the PSRT class XI subject of Audio Video Engineering Competence at Public Vocational High School 3 Semarang has been successfully implemented. The assessment of critical aspects of the blended learning model by learning model experts shows that learning planning with the blended learning model is feasible and can be used to implement PSRT learning activities in class XI of audio-video engineering competence because it has met the criteria for implementing blended learning by covering 5 (five) keys to blended learning, namely live events, self-paced learning, collaboration, assessment, and performance support materials. Learning with the blended learning model is declared to be effective and well implemented, as can be seen from the results of increasing student learning outcomes. Learning with the blended learning model has proven to be effective in terms of learning outcomes of the PSRT that uses the blended learning model >75. There is a significant difference in learning outcomes between the group using the blended learning model and the group not using the blended learning model. The process of increasing student activity and motivation becomes better.